Flow and flow-induced vibration of a square array of cylinders in steady currents. (30th June 2015) - Zhao, Ming; Cheng, Liang; An, Hongwei; Tong, Feifei
Abstract: Flow and flow-induced vibration of a square array of cylinders are investigated by two-dimensional numerical simulations. Flow past 36 cylinders in an inline arranged square array and 33 cylinders in a staggered arranged square array is firstly simulated, for Re = 100 and the spacing ratios of L / D  = 1.5, 2, 3, 4, 5. Only one vortex street is observed in the wake of the cylinder array when the spacing ratio is 1.5 in the inline arrangement and 1.5 and 2 in the staggered arrangement, indicating that the critical spacing ratio for the single-vortex street mode in the staggered arrangement is higher than that in the inline arrangement. The vortex shedding from the cylinders is suppressed at L / D  = 3 for both inline and staggered arrangements. Vortex shedding from each individual cylinder is observed when L / D  = 4. Flow-induced vibration of 36 cylinders in an inline square arrangement is studied for a constant Reynolds number of 100, two spacing ratios of 2 and 5, a constant mass ratio of 2.5 and a wide range of reduced velocities. It is found that for a spacing ratio of 2, the vibration of the cylinders in the four downstream columns does not start until the reduced velocity exceeds 4.5. The vibration of the cylinders progresses downstream with increasing reduced velocity. For a spacing ratio of 5, the vibrations of the cylinders in the most upstream column are similar to that of a single cylinder. The vibration amplitudes of the downstream cylinders peak at higher reduced velocities than that of a single cylinder. The maximum possible response amplitudes occur at the most downstream cylinders.